A note on foreign bank investment in the USA - Esperança, J.; Gulamhussen, M. A. (Applied Financial Economics, 2002)
This study investigates the presence of panel effects in the foreign bank investment decision in the USA. To accomplish this purpose, it tests a model of the effect of home country factors on foreign bank investment in the USA. The relationship between home country factors and foreign bank investment in the USA is empirically tested through regression analysis of panel data (53 countries; 8 years). The empirical results confirm the presence of panel effects, previously ignored in the literature, and dependence of foreign bank investment in the USA on home country factors.